Penerapan Network Planning Pada Rekondisi Electric Motor Rustibus 2000 MV. Meratus Malino - Adiwijaya, Puji Alphatehah Putra Tri Surya; Tnunay, Imanuel Adam; Manesi, Damianus (Universitas Pertahanan RI, 2024)
Electric Motor or what is called as dynamo is a driving motor that converts electrical energy into kinetic energy. This energy change is carried out due to differences in the magnetic field in the coil so that when the coil is electrified, there will be a difference in the magnetic field which causes movement. Rustibus 2000 is a rust removal machine (scaling machine) that removes rust from the surface of ships. The role of the dynamo on the Rustibus is very continuous so maintenance must be scheduled and routine. Dynamo maintenance is carried out using a parallel work system and is carried out sequentially without paying attention to work priorities. Here, researchers apply the method of network planning with the CPM (critical path method) approach by looking for critical paths so that the electric motor reconditioning work which originally took 18 hours at a cost of Rp. 2,700,000 to 17.5 hours at a cost of Rp. 2,625,000.